2018
DOI: 10.1111/ggi.13588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and short‐term outcomes in patients with acute cholecystitis over aged >80 years

Abstract: Aim We investigated the clinical characteristics and short‐term outcomes in acute cholecystitis (AC) patients aged ≥80 years. We therefore sought to determine the ideal treatment for elderly patients with AC. Methods We retrospectively evaluated 253 patients with AC. The patients were divided into two groups according to their age: elderly group (n = 77, aged ≥80 years) and non‐elderly group (n = 176, aged <80 years). We compared the clinical characteristics, in‐hospital mortality and recurrence of cholecystit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This data may possibly be the result of delayed hospital admission of elderly people according to many coexisting health and social problems such as lack of health insurance or lack of transport to health care units. Akasu et al reported leucocytosis in patients with acute cholecystitis, but no significant difference between young and elderly groups while Borzellino et al reported leucocytosis in elderly patients with diagnosis of an acute cholecystitis, mean value of 15.6x10 9 /L as more similar to our study [26, 27].…”
Section: Discussionsupporting
confidence: 87%
“…This data may possibly be the result of delayed hospital admission of elderly people according to many coexisting health and social problems such as lack of health insurance or lack of transport to health care units. Akasu et al reported leucocytosis in patients with acute cholecystitis, but no significant difference between young and elderly groups while Borzellino et al reported leucocytosis in elderly patients with diagnosis of an acute cholecystitis, mean value of 15.6x10 9 /L as more similar to our study [26, 27].…”
Section: Discussionsupporting
confidence: 87%
“…With the aid of modern perioperative care and laparoscopic surgery, patients between 65 and 80 years of age are now thought to have operative risks comparable to the younger population[ 5 ]. To date, the outcomes regarding the safety of cholecystectomy performed in older patients are controversial[ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%